PENGARUH TEKNIK RELAKSASI FINGER HOLD TERHADAP INTENSITAS NYERI PADA PASIEN POST OPERASI SECTIO CAESAREA DI RUANG BERSALIN RSU LATERSIA BINJAI - Sinambela, Megawati; Tamba, Vera Wati (JURNAL ILMIAH DHDT - KEBIDANAN, 2024)
Sectio Caesarea is a way of giving birth to a fetus by making an incision in the uterine wall through the front wall of the abdomen. WHO in 2016 set the average standard for sectio caesarea in a country to be 5-15% per 1000 births in the world. Latin America and the Caribbean region contributed the highest caesarean method rates, namely 40.5%, followed by Europe 25%, Great Britain 20%, Asia 19.2%, Africa 7.3%, Indonesia 15.3% above the standard issued by WHO. At Latersia Hospital, the number of sectio caesarea deliveries in 2022 was 1058 cases. The purpose of this study was to identify the effect of the finger hold relaxation technique on pain intensity in postoperative sectio caesarea patients in the delivery room of RSU Latersiain 2023.This research is a quantitative research with a quasi-experimental research design with a one group pretest- posttest design without a control group. The sampling technique uses probability sampling which is taken by purposive sampling with a total sample of 46 respondents.The results of the wilcoxon showed that there was an effect of the finger hold relaxation technique on reducing pain intensity in postoperative sectio caesarea patients (p value = 0.000 <0.05). Most of the respondents had a moderate pain scale before the finger hold relaxation technique was carried out, and most had a mild pain scale after the finger hold relaxation technique was carried out, so it can be concluded that the finger hold relaxation technique is effective for reducing pain in postoperative sectio caesarea patients in the delivery room of RSU Latersia2023.